1999
DOI: 10.1302/0301-620x.81b3.0810420
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of shoulder instability

Abstract: The shoulder is designed for maximum mobility and is therefore the most common joint to develop instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…In line with previous studies, the SANEM showed a high correlation with CS [13, 14]. The OSS and OSIS also correlated high with the SANEM, another expected result since they both measure function and pain [10, 11]. A moderate correlation between the SST and the SANEM was found.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies, the SANEM showed a high correlation with CS [13, 14]. The OSS and OSIS also correlated high with the SANEM, another expected result since they both measure function and pain [10, 11]. A moderate correlation between the SST and the SANEM was found.…”
Section: Discussionsupporting
confidence: 90%
“…The Oxford Shoulder Instability Score is a shoulder-specific measurement which is also disease-specific for patients with instability problems. It was developed in the UK by Dawson et al in order to assess the outcome of a treatment for shoulder instability [11]. The OSIS contains 12 questions about pain and shoulder function with 5 responses for each question.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Missing data were accounted for by restricted maximum likelihood estimation. 19 Players completed 3 online PROMs after a minimum of 12 months postoperatively, including the Oxford Shoulder Score (OSS; scores range from 0 [worst] to 48), 10 the Nottingham Clavicle Score (NCS; scores range from 0 [worst] to 100), 8 and the Specific Acromioclavicular Score (SACS; scores range from 0 [best] to 100). 4 The OSS is a measure of general shoulder function, and the NCS and SACS are scores that are specific and sensitive to measuring changes in the ACJ population.…”
Section: Methodsmentioning
confidence: 99%
“…All patients who underwent rotator cuff repair surgery in our institution were assessed by a trained healthcare professional blinded to the surgical procedure performed at our orthopaedic diagnostic centre preoperatively and also post-operatively at 3, 6, 12 and 24 months. The assessment included several parameters such as numerical pain rating scale (NPRS), constant shoulder score (CSS), 6,7 Oxford shoulder score (OSS) 8,9 and University of California, Los Angeles shoulder score (UCLASS). 10 The length of operation was recorded in the operation notes after the surgery, which also included whether any concurrent biceps tenotomy or tenodesis was performed.…”
Section: Methodsmentioning
confidence: 99%